Ahlstrom-Munksjö expands testing for EV and industrial filtration. Issue 10 (October 2021) - Unknown
Abstract : Ahlstrom-Munksjö has developed new capabilities at its Pont-Evêque R&D centre in France to test gas adsorption performance, as part of the company's strategy to invest and grow in the electric vehicle and industrial filtration markets.